Patient-reported Effects of Fedratinib, an Oral, Selective Inhibitor of Janus Kinase 2, on Myelofibrosis-related Symptoms and Health-related Quality of Life in the Randomized, Placebo-controlled, Phase III JAKARTA Trial - Ruben A. Mesa; Nicolaas Schaap; Alessandro M. Vannucchi; Jean-Jacques Kiladjian; Francesco Passamonti; Sonja Zweegman; Moshe Talpaz; Srdan Verstovsek; Shelonitda Rose; Pranav Abraham; Jennifer Lord-Bessen; Derek Tang; et al. (HemaSphere, 2021)
Patients with myelofibrosis (MF) experience an array of symptoms that impair health-related quality of life (HRQoL). Fedratinib, an oral, selective Janus-kinase 2 (JAK2) inhibitor, was investigated in the randomized, placebo-controlled, phase III JAKARTA study in adult patients with intermediate- or high-risk JAK-inhibitor-naïve MF. The effect of fedratinib 400 mg/d on patient-reported MF symptoms and HRQoL in JAKARTA was assessed. Participants completed the modified Myelofibrosis Symptom Assessment Form (MFSAF v2.0), which evaluates 6 key MF symptoms (night sweats, early satiety, pruritus, pain under ribs on the left side, abdominal discomfort, bone/muscle pain). The modified MFSAF v2.0 was completed during the first 6 treatment cycles and at end of cycle 6 (EOC6). Symptom response was a ≥50% improvement from baseline in total symptom score (TSS). Overall HRQoL was assessed by EQ-5D-3L health utility index (HUI) score. The MFSAF-evaluable population comprised 91/96 patients randomized to fedratinib 400 mg and 85/96 patients randomized to placebo. Mean baseline TSS was 17.6 and 14.7 for fedratinib and placebo, respectively, and mean EQ-5D-3L HUI was 0.70 and 0.72. Fedratinib elicited statistically significant and clinically meaningful improvements in TSS from baseline versus placebo at all postbaseline visits. Symptom response rates at EOC6 were 40.4% with fedratinib and 8.6% with placebo (OR 7.0 [95% CI, 2.9-16.9]; P < 0.001), and a significantly higher proportion of fedratinib-treated patients achieved clinically meaningful improvement from baseline on the EQ-5D-3L HUI at EOC6 (23.2% versus 6.5%; P = 0.002). Fedratinib provided clinically meaningful improvements in MF symptoms and overall HRQoL versus placebo in patients with JAK-inhibitor-naïve MF.